Legal Certainy in Resolving Trademark Disputes Involving Subtantial Similarities to Registered Trademarks of Other Parties - Liansah, Irene; Sugiyono, Heru (Dinasti Research, 2025)
The increasing number of trademark registrations in Indonesia reflects a growing awareness among business actors regarding the importance of legal protection for product or service identity. However, this trend also triggers legal disputes, particularly when a newly registered trademark bears substantial similarity to an existing registered trademark. This study aims to analyze the resolution of trademark disputes involving substantial similarities to registered trademarks of other parties, and to examine the legal certainty surrounding such dispute resolution through trademark cancellation lawsuits in the Commercial Court and arbitration proceedings. The research used a normative juridical method by examining written legal norms such as legislation, court decisions, and analyzing relevant concrete cases. The results indicate that resolution through cancellation lawsuits in the Commercial Court is transparent and offers legal protection through judicial processes. However, it faces challenges such as lengthy procedures and limited judicial understanding of intellectual property. In contrast, arbitration offers a faster and more efficient alternative, yet remains underutilized due to weak contractual awareness. In terms of legal certainty, court litigation provides binding legal force through decisions that may serve as jurisprudence, while arbitration ensures certainty through final and binding awards, although enforcement remains limited. In conclusion, optimizing both avenues requires robust regulatory support and legal education for business actors